Promoting local economic development in Egypt: Challenges and lessons learned from the case of Fayoum governorate - Abozeid, Omar (AUC Knowledge Fountain, 2017)
Local Economic Development continues to emerge as an important and a viable tool for achieving economic growth, creating new jobs, increasing income level, and improving the quality of life in different local communities, in both industrialized and developing countries. There are a number of different approaches to promoting Local Economic Development (LED), yet they all share a common rationale: assessing the local economy, identifying different challenges and economic potentials, coming up with a set of proposed interventions and projects, and collaborating with different local and national actors to implement those interventions and projects. Local administrations in Egypt, however, have little experience in adopting such comprehensive strategic planning approach to plan, manage, and develop their local economies. This study adopts a qualitative research approach by analyzing in-depth interviews conducted with a number of relevant local and national actors in order to explore one of the most solid LED promotion experiences ever to take place in Egypt: Fayoum LED Promotion Experience. The study was able to identify a number of external and internal challenges that hindered the full realization of the LED promotion process objectives in Fayoum. The main recommendations to overcome those challenges as suggested by this study include: institutionalize the LED promotion process, guarantee a formal political commitment to the process, develop a national framework for LED promotion, and move towards a decentralized local administration system. The study also proposes an alternative participatory partnership-based approach; Government-Led Active Partnership Approach (GAPA), that is designed on the assumption that local administrations have to promote LED within the currently identified challenges.